Analysis of the Implementation of Green Banking Concepts in the Operations of Bank Aceh Syariah (Sisingamaraja Medan Branch) in Support of Sustainable Finance - Afni Haryanti Harahap; Fauzi Arif Lubis; Tuti Anggraini (Yayasan Pendidikan Bukhari Dwi Muslim, 2026)
Purpose: This study examines green banking implementation in the operations and financing processes of Bank Aceh Syariah, Sisingamangaraja Medan Branch, and its potential relationship with sustainable finance. Research Method: A qualitative descriptive-analytical case-study design was applied. Data were obtained through in-depth interviews with purposively selected branch employees and analyzed through reduction, coding, categorization, and evidence comparison using six Green Coin Rating indicators as a qualitative framework. Results and Discussion: Paperless operations were partially implemented through mobile banking, while electricity-saving routines represented resource conservation rather than verified carbon-emissions management. Formal green rewards, green-building standards, and reuse, recycling, and refurbishment were not demonstrated. Environmental documentation and financing restrictions indicated environmental risk screening but did not establish an active green-investment portfolio. Consequently, measurable contributions to sustainable finance could not be confirmed. Implications: The branch should establish resource-consumption baselines, formal environmental policies, circular waste procedures, green-financing criteria, and portfolio monitoring. Originality: This study provides a branch-level Islamic banking assessment that distinguishes operational efficiency, environmental screening, and active green financing while avoiding unsupported sustainability claims.